EVALUATION OF IN-VIVO ANTIDEPRESSANT ACTIVITY OF SOLID-LIPID NANOPARTICLES OF ALBIZZIA LEBBECK[L] - Kavitha S K, Dr. Mohammad Ali (Chelonian Research Foundation, 2024)
The extraction of Albizzia lebbeck with ethanol were done and the percentage yield was calculated based on the dry weight of the extract.by using these methods to perform the phytochemical investigation of Albizzia lebbeck showed in the presence of alkaloids, carbohydrates, proteins, tannins, flavonoids and amino acids. Solid lipid nanoparticles of ethanolic extract Albizia lebbeck leaf extract were prepared by Co-Precipitation method. Various Behavioural studies through In-vivo antidepressant activity of the prepared nanoparticles 100mg/kg,200mg/kg,400mg/kg were done by tail suspension model, forced swimming model, open field model, locomotion model. Significant reduction in the depressive behaviour of Swiss albino mice were observed with decreased immobility in tail suspension model, increasing climbing & swimming in forced swimming model, increasing number of lines crossing in open field model and increasing count in locomotion model compared to control (Normal saline). may enhance mood depression-related behaviours, &, after behavioural parameter the Rats were sacrificed for Favourable histopathological findings—such as reduced neuronal damage, less inflammation, or normalization of brain structure in depression-related regions (e.g., hippocampus or prefrontal cortex)—support the antidepressant and neuroprotective effects of the compound and compared with standard drug Imipramine (15mg/ kg B.W). These findings indicate that the formulated solid lipid nanoparticles of Albizia lebbeck leaf extract have restored or protected brain tissue integrity. As depression is associated with various biochemical parameters, hence the study was continued for the estimation of oxidative stress, glutathione content, [18.48+_0.57μg/g wet tissue 17,35+0.72μg/g wet tissue) superoxide dismutase [35.29+_0.63U/ml of protein,34.56+_0.86U/ml], catalase 1.39+_0.026μg/g of protein,1.26+_0.015μg/g protein] acetylcholinesterase. (56.43+_3.25 moles/min/mg tissue,49.57+_3.67 moles/min/mg tissue]